1996
DOI: 10.1128/iai.64.4.1314-1320.1996
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-12 and tumor necrosis factor alpha mediate innate production of gamma interferon by group B Streptococcus-treated splenocytes of severe combined immunodeficiency mice

Abstract: The existence of interleukin-12-mediated innate immune responses to group B streptococci (GBS) was tested by examining T-lymphocyte-independent gamma interferon (IFN) production in cultured splenocytes from severe combined immunodeficiency mice. Splenocytes were cultured with killed or living GBS for 48 h, and then IFN was measured by enzyme-linked immunosorbent assay. Type III GBS as well as other extracellular bacterial agents of neonatal sepsis (staphylococci and enterococci) induced IFN production, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 27 publications
4
10
0
Order By: Relevance
“…The exposure of macrophages to group B Streptococcus and other extracellular bacterial agents of Staphylococci and Enterococci result in the production of bioactive IL‐12 [13]. In our study, a reduction of IL‐12 production was seen by pre‐treatment of the bacteria with GA or by heat.…”
Section: Discussionsupporting
confidence: 46%
“…The exposure of macrophages to group B Streptococcus and other extracellular bacterial agents of Staphylococci and Enterococci result in the production of bioactive IL‐12 [13]. In our study, a reduction of IL‐12 production was seen by pre‐treatment of the bacteria with GA or by heat.…”
Section: Discussionsupporting
confidence: 46%
“…Lane designations are identical for blots and histograms. [51]. These investigators also suggested that IFN-g could have a role in non-specific resistance to GBS, inducing feedback activation of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a previous report examining the role of complement in determining the phagocytosis of GBS-III by peritoneal murine macrophages in the absence of immune serum, has underlined that C3-dependent binding may be important for mononuclear phagocyte-dependent clearance of GBS from the blood of patients with a deficiency of type-specific antibodies [60]. Other authors, on the basis of results obtained in an animal model of in vitro GBS-III infection, have suggested that activation of NK cells with IFN-g release could be a critical event, during in vivo infection, in promoting bactericidal functions of neutrophils and macrophages [51,61,62]. Contrary to these speculations, in our experimental model, the increase of important functions of the natural immune system, such as splenic NK activity and microbicidal activity of splenic mononuclear and polymorphonuclear phagocytes induced in vivo by GBS-Ia, did not seem to have any effect on resistance to infection, which in fact rapidly became lethal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations